2023
DOI: 10.1111/liv.15556
|View full text |Cite
|
Sign up to set email alerts
|

Fatty liver disease, heart rate and cardiac remodelling: Evidence from the UK Biobank

Abstract: Background and Aims: Growing evidence supports an association between fatty liver disease (FLD) and cardiac dysfunction and remodelling, leading to cardiovascular disease and heart failure. Herein, we investigated the independent contribution of FLD to cardiac dysfunction and remodelling in participants from the UK Biobank with cardiac magnetic resonance (CMR) data available.Methods: A total of 18 848 Europeans without chronic viral hepatitis and valvular heart diseases, with liver magnetic resonance imaging a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
2
7
0
1
Order By: Relevance
“…34,35 A recent large and elegantly conducted study using data from the UKBB showed that NAFLD is an independent predictor of higher HR and early cardiac remodelling associated with reduced ventricular volumes. 36 Second, our study suggests that the role of liver fibrosis on the effect by which obesity might potentially influence arterial hypertension is still inconclusive. For example, by constructing a mediation analysis, we did not observe any effect of liver fibrosis (non-invasively estimated by NFS) on the relationship between BMI and blood pressure in the young population of the BHS.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…34,35 A recent large and elegantly conducted study using data from the UKBB showed that NAFLD is an independent predictor of higher HR and early cardiac remodelling associated with reduced ventricular volumes. 36 Second, our study suggests that the role of liver fibrosis on the effect by which obesity might potentially influence arterial hypertension is still inconclusive. For example, by constructing a mediation analysis, we did not observe any effect of liver fibrosis (non-invasively estimated by NFS) on the relationship between BMI and blood pressure in the young population of the BHS.…”
Section: Discussionmentioning
confidence: 81%
“…Elevated pulse pressure has been shown to provide independent prognostic information on CV mortality and multiple adverse CV outcomes in population‐based studies 34,35 . A recent large and elegantly conducted study using data from the UKBB showed that NAFLD is an independent predictor of higher HR and early cardiac remodelling associated with reduced ventricular volumes 36 …”
Section: Discussionmentioning
confidence: 99%
“…All participants gave written informed consent to the study. Federica Tavaglione 1,2 Oveis Jamialahmadi 1 Charlotta Ljungman 1,3 Stefano Romeo 1,3,4 1 Department of Molecular and Clinical Medicine, Sahlgrenska…”
Section: Co N Fli C T O F I Nter E S T S Tatem Entmentioning
confidence: 99%
“…We thank Boeckmans and Schattenberg for their positive comments on our published work 1 where we demonstrated that fatty liver disease (FLD) is associated with (a) higher heart rate (beta coefficient 0.364, p < .001) and cardiac remodelling (beta coefficient 0.433 and −0.406, for eccentricity ratio and remodelling index, respectively, p < .001) and (b) with reduced ventricular volumes independently of traditional metabolic and cardiovascular risk factors. Notably, the analysis included more than 18 000 Europeans from the UK Biobank study with liver magnetic resonance imaging proton density fat fraction (MRI‐PDFF) and cardiac magnetic resonance (CMR) data available.…”
Section: Cmr Endpoints Fni < 033 (N = 14 745) Fni ≥ 033 (N = 662) βEt...mentioning
confidence: 99%
See 1 more Smart Citation